Patient’s effective dose and performance assessment of computed radiography systems - Bushra, A.; Sulieman, A.; Edam, A.; Tamam, N.; Babikir, E.; Alrihaima, N.; Alfaki, E.; Babikir, S.; Otayni, Ahmed; Alkhorayef, M.; Abdelradi, A.; Bradley, D.A. * (Elsevier, 2022)
Computed tomography is widely used for planar imaging. Previous studies showed that CR systems involve higher patient radiation doses compared to digital systems. Therefore, assessing the patient’s dose and CR system performance is necessary to ensure that patients received minimal dose with the highest possible image quality. The study was performed at three medical diagnostic centers in Sudan: Medical Corps Hospital (MCH), Advance Diagnostic Center (ADC), and Advance Medical Center (AMC). The following tools were used in this study: Tape measure, Adhesive tape, 1.5 mm copper filtration (>10 × 10 cm), TO 20 threshold contrast test object, Resolution test object (e.g., Huttner 18), MI geometry test object or lead ruler, Contact mish, Piranha (semiconductor detector), Small lead or copper block (~5 × 5 cm), and Steel ruler, to do a different type of tests (Dark Noise, Erasure cycle efficiency, Sensitivity Index calibration, Sensitivity Index consistency, Uniformity, Scaling errors, Blurring, Limiting spatial Resolution, Threshold, and Laser beam Function. Entrance surface air kerma (ESAK (mGy) was calculated from patient exposure parameters using DosCal software for three imaging modalities. A total of 199 patients were examined (112 chest X rays, 77 lumbar spine). The mean and standard deviation (sd) for patients ESAK (mGy) were 2.56 ± 0.1 mGy and 1.6 mGy for the Anteroposterior (AP) and lateral projections for the lumbar spine, respectively. The mean and sd for the patient’s chest doses were 0.1 ± 0.01 for the chest X-ray procedures. The three medical diagnostic centers’ CR system performance was evaluated and found that all of the three centers have good CR system functions. All the centers satisfy all the criteria of acceptable visual tests. CR’s image quality and sensitivity were evaluated, and the CR image is good because it has good contrast and resolution. All the CR system available in the medical centers and upgraded from old X-ray systems to new systems, has been found to work well. The patient’s doses were comparable for the chest X-ray procedures, while patients’ doses from the lumbar spine showed variation up to 2 folds due to the variation in patients’ weight and X-ray machine setting. Patients dose optimization is recommended to ensure the patients received a minimal dose while obtaining the diagnostic findings.